The state perspective: migrants and points of view in pedagogical material by the Ministry of Education of the Argentine Republic (Praxis Educativa, 2025)
We analyze the construction of the point of view in materials produced by the Ministry of Education of Argentine regarding topics about migration. This study allowed us to investigate questions such as who are or who may be those that migrate, who can constitute as subject of knowledge and who is relegated to the position of object of knowledge, and from what distance and angle of vision (considering the axes of power and solidarity) they are observed and studied. We inscribe our research in Critical Discourse Analysis and use a qualitative methodology that analyzes an extensive limited corpus. Among the results obtained, we highlight that the point of view of non-migrants predominates and an intimate distance coexists, which involves details of daily life, needs and desires of people who migrate, with a public distance. This generalizes and homogenizes experiences. Through these devices, the presence of migrant students in Argentine schools is made invisible. Keywords: discourse analysis; pedagogical discourse; migrants; point of view; decolonial studies
Keywords: discourse analysis; pedagogical discourse; migrants; point of view; decolonial studies